Services in the field of electronic communications and their impact on the income accounting system - Benko, Vitaliy (Herald of Economics, 2024)
Introduction. Recommendations for forecasting the activities of companies and obtaining income in the field of electronic communications in the conditions of martial law are given and developed. It is noted that communication operators are faced with new problems that require changes in approaches to conducting business, the introduction of new modern types of services, improvement of approaches to the organization of revenue accounting and other rather important issues that will provide an opportunity to remain competitive in the market of telecommunications services in the following years.Brief Literature Review. Basic studies of the concept of «income» give grounds for asserting that the specified definition develops taking into account changes in legislative acts and a clear practical direction inherent in it. Differences in the interpretation of the mentioned concept according to national and international practice create problems, and therefore require further research.Purpose. The purpose of the study is to study the features of the provision of services in the field of electronic communications and their impact on the income accounting system.Methodology. In order to solve the tasks, the methods of scientific abstraction, modeling, generalization and comparison were applied. Analysis and improvement of the methods of recognition of the date of establishment of income makes it possible to effectively manage their amount.Main results of the study. According to the results of the conducted research, it should be noted that the field of electronic communications should be considered as one of the most promising fields of activity. This is due to significant changes in the demand for services in this area and a significant increase in costs for the promotion of specific services, the emergence of new information carriers, which significantly expand the possibilities for the promotion of services. Therefore, the results of the research presented in the article give grounds for asserting that it is necessary to carry out a detailed classification of services in the field of electronic communications in order to establish their optimal volumes when calculating the cost price and substantiating the general principles of their application in accordance with modern service markets.Conclusions and prospects for further exploration. Prospects for further research should be focused on a detailed study of types of income and it should be noted that depending on the type of paid services, they affect the amount of income in different ways. Given the fact that the nomenclature of paid services is quite diverse and involves the combination of a significant number of items, it is necessary to calculate the received income in a differentiated manner. When it comes to revenues from the provision of ordinary services, they tend to decrease, because the share of rural telephone communication, landline fixed telephony is constantly decreasing. If we consider revenues from Internet services, then they are growing, because their spectrum is constantly expanding.